Neurogranin: A Potential Biomarker of Neurological and Mental Diseases - Xiang, Yang; Xin, Jiayan; Le, Weidong; Yang, Yongjian (Frontiers in Aging Neuroscience, 2020)
Neurogranin (Ng) is a small protein usually expressed in granule-like structures in pyramidal cells of the hippocampus and cortex. However, its clinical value is not fully clear so far. Currently, Ng is proved to be involved in synaptic plasticity, synaptic regeneration, and long-term potentiation mediated by the calcium- and calmodulin-signaling pathways. Due to both the synaptic integrity and function as the growing concerns in the pathogenesis of a wide variety of neurological and mental diseases, a series of researches published focused on the associations between Ng and these kinds of diseases in the past decade. Therefore, in this review, we highlight several diseases, which include, but are not limited to, Alzheimer’s disease, Parkinson disease, Creutzfeldt–Jakob disease, neuro-HIV, neurosyphilis, schizophrenia, depression, traumatic brain injury, and acute ischemic stroke, and summarize the associations between cerebrospinal fluid or blood-derived Ng with these diseases. We propose that Ng is a potential and promising biomarker to improve the diagnosis, prognosis, and severity evaluation of these diseases in the future.